2018
DOI: 10.1101/480459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Meta-Analysis of Alzheimer’s Disease Brain Transcriptomic Data

Abstract: BackgroundMicroarray technologies have identified imbalances in the expression of specific genes and biological pathways in Alzheimer's disease (AD) brains. However, there is a lack of reproducibility across individual AD studies, and many related neurogenerative and mental health disorders exhibit similar perturbations. We are yet to identify robust transcriptomic changes specific to AD brains. This study meta-analysed publicly available brain-related disorders along with healthy cognitive individuals to deci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 75 publications
1
29
0
Order By: Relevance
“…The comparison between vehicle-treated NTG and APP/PS1 mice identified 3320 differentially expressed genes (DEGs) ( . Processes affected by the disease in APP/PS1 mice overlap with pathways well-established in AD patients including ATP metabolism, ion transport, nervous system development, synaptic transmission, and inflammation [51][52][53][54][55][56] ( Supplementary Fig. 13b).…”
Section: App/ps1mentioning
confidence: 99%
“…The comparison between vehicle-treated NTG and APP/PS1 mice identified 3320 differentially expressed genes (DEGs) ( . Processes affected by the disease in APP/PS1 mice overlap with pathways well-established in AD patients including ATP metabolism, ion transport, nervous system development, synaptic transmission, and inflammation [51][52][53][54][55][56] ( Supplementary Fig. 13b).…”
Section: App/ps1mentioning
confidence: 99%
“…10b. Processes affected by the disease in APP/PS1 mice overlap with pathways well-established in AD patients including ATP metabolism, ion transport, nervous system development, synaptic transmission, and inflammation [49][50][51][52][53][54] (Extended Data Fig. 10b).…”
Section: Cp2 Treatment Activates Translational Neuroprotective Mechanmentioning
confidence: 99%
“…A recent study identified common viral species in normal and ageing brains, with an increased human herpesvirus 6A and human herpesvirus 7 in AD brains [48]. In addition, a recent transcriptomic meta-analysis study identified genes involved with “ interspecies interactions ” were specifically enriched in AD brains when taking into account expression changes in related neurological disorders [49]. The current observation extends the previous suggestions of viral involvement in AD brains to blood, as the expression of blood-derived genes involved in the “ Herpes simplex infection” can be used to distinguish AD from other neurological diseases and control subjects in this study.…”
Section: Discussionmentioning
confidence: 99%